EFFECTIVENESS OF DIGITAL TOOLS FOR ANALYSIS AND FORECASTING IN THE FIELD OF INTERNATIONAL ECONOMY - ZHANG, Heng (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Digital tools for analysis and forecasting in the international economy [1] are a set of technological solutions based on the processing of large amounts of data, mathematical models and artificial intelligence that allow studying the dynamics of economic processes on a global scale and predicting future trends. They combine modern data processing technologies such as machine learning, Big Data, artificial intelligence algorithms and econometric models to analyse complex economic relationships and interactions between countries, multinational companies and financial markets. In this context, these tools are becoming the basis for strategic decision-making by governments and businesses, helping to better understand global economic processes and predict future market changes.Digital analytics and forecasting tools allow modelling various scenarios for the global economy, taking into account a wide range of factors, such as changes in global trade, currency fluctuations, redistribution of investment flows and political events. As such, these tools allow for the efficient use of data to assess potential risks and opportunities, making them extremely useful in times of global economic uncertainty. In addition, they help optimize evidence-based economic decisions by providing more accurate and informed forecasts.
Keywords: Digital tools; Big Data technologies; Interpretability digital technologies